(untitled) (ETNOSIA : Jurnal Etnografi Indonesia, 2022)
This paper aims to present a different perspective on presenting patriarchal bargains from the existing ones. The patriarchal system is generally understood as a system that places men as superior to women. In the western view, the patriarchal system has become a ’way of life which is considered ahistorical, eternal and the subordination of women is a universal act, so this hierarchy has always existed and will continue, and like other natural rules, this rule is also unchangeable and unnecessary. questioned again. Radical feminists embrace and apply classical patriarchal theory to explain almost all forms of male domination over the exploitation of women. However, women’s responses to male domination vary widely, according to the objective opportunities available under each patriarchal variant, thus through patriarchal bargaining, Kandiyoti opens up opportunities for women to see patriarchy as an entity that is not eternal. Patriarchal bargain studies have also emerged with the dominance of a strong agency character. The agency character is indeed considered to have the power to target other forces outside the structure, but this becomes problematic because patriarchal bargain studies seem to ignore the existence of (partial) structure. While according to Giddens, agency plays in the realm of structure, just as the structure is an unavoidable epistemic aspect in social science, the structure is not conceptualized as only placing constraints on human agency, but is also seen as possible. Social change cannot be seen partially, both structure and agency are present simultaneously and interactively.